Regenerative Medicine - S Choudhery, Mahmood (IntechOpen, 2020)
Regenerative medicine is a promising interdisciplinary field that applies basic principles of engineering and life sciences to repair, replace, or regenerate damaged or lost tissues and organs. Unlike conventional medicine, regenerative medicine uses human cells and other substances to regrow tissues or restore their functions. Regenerative medicine combines approaches such as the use of cell-based, cell-free soluble molecules, stem cells from different sources, gene therapy, tissue engineering, reprogramming of cells, and, more recently, cell-free regenerative therapies. Regenerative Medicine provides details of the recent advancements in regenerative therapies for regenerative medicine applications.